2014
DOI: 10.1007/s11240-014-0534-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of free and glycosylated isoflavones in in vitro soybean (Glycine max L.) hypocotyl cell suspensions and comparison with industrial seed extracts

Abstract: Glycine max is one of the major sources of phytochemicals, in particular of isoflavones, a class of phytoestrogens with ascertained beneficial effects on human health. In the present study, in vitro callus production from soybean hypocotyl seedling explants and cell suspensions were optimized. Time-courses having 20, 40 and 60 g/L of initial cell inoculum were performed to determine the concentration most suitable for isoflavone production. The amount of total polyphenols and total flavonoids as well as the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Quantification of Total Flavonoid Contents. Total flavonoid contents in methanolic extracts of soybean suspension cells were quantified as described by Sansanelli et al 27 A suitable volume of methanolic extract was diluted to 400 μL with water and combined with 30 μL of 5% (w/v) NaNO 2 solution. After 5 min of incubation, 30 μL of 10% (w/v) AlCl 3 was added to the mixture.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Quantification of Total Flavonoid Contents. Total flavonoid contents in methanolic extracts of soybean suspension cells were quantified as described by Sansanelli et al 27 A suitable volume of methanolic extract was diluted to 400 μL with water and combined with 30 μL of 5% (w/v) NaNO 2 solution. After 5 min of incubation, 30 μL of 10% (w/v) AlCl 3 was added to the mixture.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the current study, the total phenolic content of soy cell extract was determined as 275 ± 13.3 µM GAE/g extract. In a similar research, Sansanelli et al [27] investigated the effect of cell inoculation rate of soy suspensions on the total amount of phenolic compounds. They reported that the highest total phenolic amount was obtained as 36.2 mg GA equivalent /L in 40 grams/L inoculated suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Many suspension-cultured cell lines of soybean have been derived from different cultivars (Gamborg et al 1968), and their isoflavonoid contents have been analyzed (Ames and Worden 1997;Federici et al 2003;Ikeda et al 1979;Sansanelli et al 2014). Moreover, several studies have focused on the effects of biotic and abiotic stresses on isoflavonoid biosynthesis in soybean suspension-cultured cells (Akashi et al 2009;Fett and Zacharius 1982;Hille et al 1982;Kochs et al 1987;Zacharius and Kalan 1990).…”
mentioning
confidence: 99%